1985
DOI: 10.1021/j100260a034
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium isotope effects in condensed-phase thermochemical decomposition reactions of octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine

Abstract: The deuterium isotope effect was applied to condensed-phase thermochemical reactions of HMX and HMX- Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…In every case, the same mechanistic rate-controlling bond rupture found in the ambient pressure decomposition process for each compound, proved to be a significant ratecontrolling mechanistic feature observed in rapid deflagration [8,14], high-pressure combustion [14][15][16], and thermal explosion events [3,14]. Furthermore, it is detected as being a significant contributing mechanistic feature in impact or shock explosive initiation sensitivity [12,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In every case, the same mechanistic rate-controlling bond rupture found in the ambient pressure decomposition process for each compound, proved to be a significant ratecontrolling mechanistic feature observed in rapid deflagration [8,14], high-pressure combustion [14][15][16], and thermal explosion events [3,14]. Furthermore, it is detected as being a significant contributing mechanistic feature in impact or shock explosive initiation sensitivity [12,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 84%
“…The seminal KDIE-based thermochemical decomposition investigation of a heterocyclic nitramine was accomplished with HMX and HMX-d 8 and revealed a different KDIE and ratecontrolling mechanistic step dependence on the HMX physical state [8]. This IDSC study showed a rate-controlling C H bond rupture occurred during solid state decomposition along with other rate-controlling features in the mixed-melt and liquid state decompositions.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations